Extreme dislocation-mediated plasticity of yttria-stabilized zirconia. (January 2022) - Liang, Chunyuan; Tong, Ke; Huang, Junquan; Bu, Yeqiang; Liu, Jiabin; Zhao, Zhisheng; Wang, Lin; Xu, Bo; Liu, Zhongyuan; Wang, Yanbin; Nie, Anmin; Wang, Hongtao; et al.
Abstract: Ceramics constitute a major class of engineering materials, but their applications are severely undercut by the propensity to catastrophic brittle fracture. Due to the brittleness and sensitivity to flaws, dislocation-mediated plasticity is rarely achieved in ceramics at room temperature. Here, we report in-situ mechanical testing on oriented submicron single-crystal pillars of cubic yttria-stabilized zirconia (YSZ) in the transmission electron microscope, to show that ultra-large plastic deformation mediated by dislocations can be achieved at room temperature. By employing three-dimensional tomography and atomic imaging, unprecedented details of spatial features of the generated dislocations are demonstrated. While deformation in pillars compressed along <111> directions is achieved by dislocation slip on the non-close-packed 001 planes, strains in those compressed along <001> are by slip on the close-packed 111 planes. Different dislocation slips cause obvious anisotropy in mechanical properties of YSZ crystal. The <111> pillars exhibit much greater plastic deformability than the <001> pillars, with observed strains as high as 61.6%. These results may lead to potentially new applications of YSZ at submicron scales and provide important insights into deformation mechanisms of ionic ceramics in general. Graphical abstract: Image 1 Highlights: Exceptionally large plastic strain has been achieved in submicron yttria-stabilized zirconia crystals at room temperature. Dislocation slips on 001 and 111 planes are demonstrated with unprecedented details by three-dimensional tomography. Different dislocation slips cause obvious anisotropy in mechanical properties of yttria-stabilized zirconia crystal. The non-conventional slip systems in cubic YSZ shed new light on fundamental deformation mechanisms of ionic crystals.